Students’ Opinion on the Existing Educational Standard; A Study of the University of Horticulture and Forestry (UHF), Nauni- Solan (H.P.) - Sharma, D D; Gupta, Hitesh; Bhardwaj, Abhay; Jharate, Amit (Indian Journal of Extension Education, 2021)
The study conducted on 100 students randomly selected from under -graduate and post-graduate faculty of Dr.Â Y.S. Parmar university of Horticulture and Forestry Nauni- Solan (H.P.) revealed that a cordial and good relationship existed between the teachers and the taught as well as male and female students in the university. Overall rating of the students on teaching standard in the university was found to be good. More emphasis on theory, taking theory classes in practical hours, inferiority complex among the students, fast delivery of the lectures by theÂ teachers, unfriendly environment in the class, discouraging students feedback/questioning etc. were some ofÂ the main problems/difficulties faced by them. The study implies that the teachers should teach the students as per their learning capability /styles giving more emphasis on practical knowledge rather than the theoretical knowledge besides motivating them to participate in sports, games and other extra- curricular activities in orderÂ to further improve the existing education standard in the university. Sincere efforts should also be made to harness the talents of the students by organising various training programmes, workshops, seminars and orientation programmes for them.